Comparative Analysis of Polynomial Zeroes within Prescribed Bounds - V.R.Patil, Peerzada Naveed Ahad (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper presents a comparative study of zeroes of two distinct polynomials under specified bounds. The investigation focuses on understanding the behavior of polynomial roots within predefined bounds and elucidating the implications of such constraints on their properties.